Eccentric/Exzentrisch: On Gould, Gulda, and Becoming a Cultural Icon - Carpenter, Alexander (Intersections, 2017)
This article considers how cultural icons are formed and compares the cultural backgrounds, careers, and reputations of two of the most talented—if most “eccentric”—classical musicians of the twentieth century: Canadian pianist and broadcaster Glenn Gould, and Austrian pianist, composer, and provocateur Friedrich Gulda. Gould is a celebrated Canadian icon whose well-publicized eccentricities as a musical interpreter and an individual count favourably towards his iconic status; Gulda, while a pianist of similar skill and accomplishments, is regarded as an ambivalent—if not scandalous—figure in Austrian cultural history, precisely because of his eccentric behaviour and genre-bending performances.